Effect of surfactants on the convective heat transfer and pressure drop characteristics of ZnO/DIW nanofluids: An experimental study - Adnan Qamar (14421759) (2023)
The advancement of nanotechnology has demonstrated the ability of metal-oxide-based nanofluids (NFs) to produce high heat flux in microscale thermal applications. Convective heat transfer (HTC) and flow characteristics (pressure drop (ΔP) and friction factor (f)) of aqueous ZnO NFs' within a circular mini tube (D i = 1.0 mm, L = 330 mm) were analyzed. Experiments were carried out under steady-state and varying flow rates using 0.012–0.048 wt % of NFs and sodium hexametaphosphate (SHMP) and acetylacetone (ACAC) as surfactants (SFs). Laminar flow and constant wall heat flux conditions were used to assess NFs heat transfer properties, ΔP and f. The viscosity (VC) and thermal conductivity (TC) of NFs exhibited a strong dependence on the operating temperature and NFs concentration. VC and TC increased by increasing the NFs concentration and decreased by increasing the operating temperature. Maximum VC and TC enhancement of 16.75% and 23.70% were achieved for SHMP-stabilised NFs, respectively. The average HTC increased by increasing NFs loading and flow rate, with HTCmax of 17.0% noticed for ACAC-stabilised NFs. The ΔPmax and f max were 16.0% and 12.0%, respectively. Experimental and theoretical results showed a maximum deviation of ±7.0% and ±4.0%, respectively. Other Information Published in: Case Studies in Thermal Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.csite.2023.102716